Fast Turbulent Flames in Duct-Vented Gas Explosion - R.M. Kasmani; G. Andrews; H.N. Phylaktou; M.H. Hashim; N. Ibrahim; R.R. Ali; H. Hasbullah (Chemical Engineering Transactions, 2013)
The influence of vent ducts on gas explosions was investigated with the aim of determining whether the use of larger area of the vent duct than the vent, would reduce the overpressure in vented duct explosion. A 0.2 m3 cylindrical vessel was used with L/D (length to diameter) of 2, at the limit of applicability of current explosion venting design guidance. Only end ignition was considered in this study with a vent coefficient, K of 16.4. Methane/air mixtures over a range of equivalence ratio, ? (0.68, 0.84 and 1.05) have been used. Results showed that while there is no significant difference in maximum pressure for larger vent duct as compared to a free discharge vent at lean mixtures, however, a significant increase of overpressure ~?1.4 bar was obtained in reactive mixtures i.e. ? =1.05. This was due to the high unburnt gas velocities induced in the vent duct by the most reactive explosion, creating very high turbulence levels at the vent duct inlet which gave rise to very fast flames and very high back pressures. Flame speeds in the vent duct of up to 500 m/s were measured for the most reactive mixture in the larger vent duct. The results were not predicted by the current US and European vent design guidance.